x e *sin(x) - 1
d / x \ --\e *sin(x) - 1/ dx
Differentiate exsin(x)−1e^{x} \sin{\left(x \right)} - 1exsin(x)−1 term by term:
Apply the product rule:
f(x)=exf{\left(x \right)} = e^{x}f(x)=ex; to find ddxf(x)\frac{d}{d x} f{\left(x \right)}dxdf(x):
The derivative of exe^{x}ex is itself.
g(x)=sin(x)g{\left(x \right)} = \sin{\left(x \right)}g(x)=sin(x); to find ddxg(x)\frac{d}{d x} g{\left(x \right)}dxdg(x):
The derivative of sine is cosine:
The result is: exsin(x)+excos(x)e^{x} \sin{\left(x \right)} + e^{x} \cos{\left(x \right)}exsin(x)+excos(x)
The derivative of the constant (−1)1\left(-1\right) 1(−1)1 is zero.
Now simplify:
The answer is:
x x cos(x)*e + e *sin(x)
x 2*cos(x)*e
x 2*(-sin(x) + cos(x))*e